Implementasi Akuntabilitas dan Transparansi Keuangan Masjid Baiturrahman Berbasis Digitalisasi Sederhana dan Pengendalian Internal - Aziza Aziza; Az-Zahra Nayla Rosa; Syallom Marcellino Tamauka; Rudy Usman; Andi Mattulada Amir (AKUNTANSI 45, 2026)
Mosque financial management currently demands high professionalism and transparency along with the significant public funds collected through Islamic philanthropic instruments. This research is a descriptive qualitative study that aims to analyze how the integration of simple information technology and internal control systems at the Baiturrahman Mosque Perdos Untad can achieve accountable and transparent financial governance. The results show that the administrators of the Baiturrahman Mosque have undergone a digital transformation by shifting from manual recording to using Microsoft Excel to process both routine and construction funds. The accountability aspect is strengthened through the implementation of internal controls in the form of a clear segregation of duties between fund receivers and the recording department, as well as a risk mitigation policy by limiting the cash-on-hand balance to a maximum of IDR 3,000,000. Furthermore, transparency is optimized by utilizing WhatsApp social media to distribute financial reports periodically to the congregation. The integration of digital tools and disciplined internal control has proven capable of increasing donor trust and fulfilling the spirit of public sector accounting standards (ISAK 35) in managing non-profit entities.